2016
DOI: 10.1080/15402002.2016.1173554
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drinks and Binge Drinking Predict College Students’ Sleep Quantity, Quality, and Tiredness

Abstract: This study examines whether energy drink use and binge drinking predict sleep quantity, sleep quality, and next-day tiredness among college students. Web-based daily data on substance use and sleep were collected across four semesters in 2009 and 2010 from 667 individuals for up to 56 days each, yielding information on 25,616 person-days. Controlling for average levels of energy drink use and binge drinking (i.e., 4+ drinks for women, 5+ drinks for men), on days when students consumed energy drinks, they repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 68 publications
5
39
0
2
Order By: Relevance
“…Previous research in this area has suggested use of energy drinks by college students could contribute to a number of adverse outcomes. For example, it has been suggested energy drink consumption by college students is associated with lower sleep quantity and quality as well as next day sleepiness [19]. It has also been suggested that episodic (binge) alcohol use is associated with energy drink consumption among college students [15].…”
Section: Present Studymentioning
confidence: 99%
“…Previous research in this area has suggested use of energy drinks by college students could contribute to a number of adverse outcomes. For example, it has been suggested energy drink consumption by college students is associated with lower sleep quantity and quality as well as next day sleepiness [19]. It has also been suggested that episodic (binge) alcohol use is associated with energy drink consumption among college students [15].…”
Section: Present Studymentioning
confidence: 99%
“…[1][2][3][4][5] It is questionable, however, whether students fully comprehend the negative consequences of sleep deficiency on physical wellbeing, emotional health, and their capacity for critical cognitive skills such as learning, memory, and problem-solving. 1,2 In higher education students, sleep deficiency has been linked to risk-taking behaviours, depression, anxiety, and decreased selfefficacy, 2,3,6 substance misuse, 3 excessive alcohol and caffeine consumption, 7,8 and high rates of social media use. 9 Insufficient sleep has also been shown to increase the long-term risk of chronic diseases such as heart disease and diabetes, 10 and is increasingly connected with neurodegenerative conditions such as dementia and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep has long been known to serve a restorative function, with shorter sleep duration associated with greater next-day tiredness (Moore et al, 2001; Patrick et al, 2016; Zisapel, 2007). We observed no age differences in the association between sleep duration and next-day tiredness, suggesting that the restorative power of sleep pervades at both younger and older ages.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the laboratory study designs allow participants to get a full night of sleep. In daily life, however, alcohol use and sleep deprivation are often experienced together due to work, family, and other demands (Patrick et al, 2016; Verster, 2008). …”
Section: Discussionmentioning
confidence: 99%